Direct inkjet-patterning of energy efficient flexible electrochromics. (July 2018) - Cai, Guofa; Cheng, Xing; Layani, Michael; Tan, Alvin Wei Ming; Li, Shaohui; Eh, Alice Lee-Sie; Gao, Dace; Magdassi, Shlomo; Lee, Pooi See
Abstract: High-quality patterns were successfully prepared by inkjet-printing WO3 -PEDOT:PSS composites on different substrates including the rigid FTO glass and most importantly, on flexible PEDOT:PSS/Ag grid/PET. Excellent electrochromic performances can be achieved, including large optical modulation (85.7% optical contrast at the wavelength of 633 nm on FTO glass substrate), fast switching speed (coloration/bleaching time of 2.4/0.8 s on the PEDOT:PSS/Ag grid/PET substrate), instantaneous coloration efficiency (68.8 cm 2 C −1 ) and good cycling stability (up to 10, 000 cycles). The effects of the applied potential window during electrochemical evaluation on the electrochromic performances were analyzed in detail. The printed electrochromics films on PEDOT:PSS/Ag grid/PET showed the best electrochemical stability, in agreement with its superior conductivity and transmittance at 633 nm of 0.6 Ω/sq and 66%, respectively. It sustained transmittance modulation of about 75.5% and 53.1% of its first cycle recorded contrast at 633 nm, after being subjected to 1000 and 5000 cycles, respectively, and maintained good electrochemical stability up to 10, 000 cycles. Moreover, a robust mechanical stability was also achieved by the printed films on flexible PEDOT:PSS/Ag grid/PET substrate. The film maintained a transmittance modulation of 85.8% of its original contrast after 5000 bending cycles at a curvature radius of 1 cm. The inkjet-printed WO3 nanocomposite based flexible electrochromic displays exhibited excellent electrochromic performance, making it a promising candidate for energy efficient displays, e-books, e-cards and multifunctional electronic devices. Graphical abstract: fx1 Highlights: High-quality electrochromic patterns were successfully prepared by inkjet printing method. The inkjet printed flexible electrodes present outstanding electrochromic performance. The flexible electrochromic displays were assembled by the inkjet printed electrodes.